Efektifitas Program Diklat Microsoft Word untuk Meningkatkan Pelayanan Publik di Bojonegoro - Abidin*, Zainul; Efendi, Agus; Santosa, Eka Budhi (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
Public affairs programs have long aimed to advance public services. One of the programs that support public services is the Microsoft Word training program but it has received less attention so that the knowledge and skills of operating Microsoft Word are lacking. According to Government Regulation No. 56 of 2005, central and local governments are responsible for developing and utilizing advances in information technology to improve local financial management as well as the dissemination of local financial information to public services. The digitalization that has made its way into everyday life is also utilized by the private sector to gain current advantages by making it easier to provide services, which can be seen in various applications such as e-government and services. The private sector is also utilizing many of these technological advancements for profit. Digital technology is simply a very fast data processing system that can produce numerical values. Activities or series of activities that meet the service needs of every citizen and resident for goods, services, and/or administrative services provided by public service providers are defined as public services. Microsoft Word Training Program is one of the technological advancements to produce improved quality, capacity, and speed of data transmission. The whole process in real life is supported by digital data.